THE IMPACT OF FRAUDULENT MARKETING PRACTICES AND EXPERIENTIAL MARKETING ON SENIORS RESISTANCE IN ADOPTING NEW TECHNOLOGIES (IN CASE OF E-COMMERCE) - Firman Pakaya, Firman Pakaya; Tasik, Hizkia H.D (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2019)
Abstract : Indonesia is one of the largest countries in the world with amount of its people that increasing massively each year. It can be seen in most of the big city in Indonesia, where the level of unemployment is high, yet the job field is narrowing to zero. It caused by phenomena where some people who live in villages go to big city, try to push their luck to get a job, hoping that it can change their life, and of course to support their family. But the reality is not what they expected. Some of them are lucky enough to get a job, even though it is a lower management position in a company, but some of them turn out to be a criminal, just to fulfill their needs, in order to survive. At the end of the day, it causing a various criminal form of action, including cybercriminals. There is an issue in Indonesia right now where fraudulent practices are increasing in E-Commerce sectors and it comes in any form, such as fraudulent by mobile texting, offering a fake promotion with big rewards, email scamming and many more. The victim itself mostly are older people with age range 50 years old until 65 years old, where they are an active smartphone user and social media addict, yet they are lack of awareness about how the fraudulent practices work. It all causing the insecurities among older people that the fraudulent practices that occur and made these type of older people resist to using e-commerce platform.Â Keywords: Fraudulent Marketing Practices, older people, experiential marketing